Comparative risk of uveitis with Janus kinase inhibitors versus tumor necrosis factor inhibitors in ankylosing spondylitis and psoriatic diseases: a target trial emulation study - Bai, Wei-Hsuan; Liao, Pei-Lun; Bai, Yi-Chiao; Wei, James Cheng-Chung (Frontiers in Immunology, 2025)
ObjectivesTo compare the risk of incident uveitis among patients with axial spondyloarthritis initiating treatment with Janus kinase inhibitors (JAKi) versus tumor necrosis factor inhibitors (TNFi).MethodsWe conducted an emulated target trial using real-world electronic health records from the TriNetX US Collaborative Network. Adults with ankylosing spondylitis (AS), psoriasis (PsO), or psoriatic arthritis (PsA) who newly initiated a JAKi or a TNFi between January 1, 2016, and December 31, 2023, were identified. Patients were stratified into JAKi and TNFi cohorts based on initial treatment exposure. Propensity score matching (1:1) was performed to balance baseline demographics, comorbidities, prior medication use, and laboratory values. Cox proportional hazards models were used to estimate hazard ratio (HR) and 95% confidence interval(CI) for the development of incident uveitis, with TNFi as the reference. Kaplan–Meier analysis was conducted to compare the 9-year cumulative incidence of uveitis between cohorts. The primary outcome was incident uveitis following initiation of therapy, with follow-up extending up to nine years.ResultsAmong 697,850 patients identified, 5,874 were included in each group after 1:1 propensity score matching. JAKi use was associated with a lower risk of incident uveitis compared with TNFi (HR = 0.630; 95% CI, 0.418–0.948). These findings remained consistent after further adjustment for comorbidities, medications, and laboratory data. Subgroup analyses showed a consistent protective association in older patients (≥ 51 years: HR = 0.43, 95% CI = 0.24–0.79), White individuals (HR = 0.59, 95% CI = 0.38–0.93), and those with elevated inflammatory markers (CRP ≥ 3 mg/L: HR = 0.50, 95% CI = 0.26–0.96; ESR ≥ 20 mm/h: HR = 0.41, 95% CI = 0.19–0.87). The reduced risk persisted regardless of concomitant use of conventional synthetic DMARDs (with csDMARDs: HR = 0.50, 95% CI = 0.28–0.92; without csDMARDs: HR = 0.56, 95% CI = 0.33–0.94).ConclusionsIn this large-scale, real-world cohort study, JAKi therapy was associated with a significantly reduced risk of incident uveitis compared to TNFi therapy in patients with AS, PsO, or PsA. These findings suggest a potential role for JAKi in mitigating ocular inflammation in this population. Further prospective studies and randomized controlled trials are warranted to validate these results and inform future clinical guidelines.